Exploring Communication Tendencies of Program Facilitators - Fawn Kurtzo; Leslie D. Edgar; Don W. Edgar; Donna L. Graham; Mark Russell (Journal of Applied Communications, 2019)
Audience analysis is a critical skill to forge relationships and develop effective communications. Programs provided by the Cooperative Extension Service must be aware of external and internal audiences to provide relevant information and evoke impacts. Berlo’s (1960) Source-Message-Channel-Receiver Model of Communications guided this formative evaluation of Extension staff, and horse 4-H club volunteer leaders (program facilitators) to expose internal communication tendencies in Arkansas. Findings identified that program facilitators seek horse-related information from a variety of sources, most frequently relying on personal connections and least frequently seeking Extension sources. Program facilitators share a variety of messages and most frequently relay information about deadlines to club members. Messages about recruitment and fundraising were shared least often. Program facilitators described utilizing a variety of personal and electronic channels to share messages with the greatest frequency for in-person communications. Incoming channels were less diverse than outgoing channels and primarily featured email, which program facilitators preferred. Program facilitators are primarily female, aged in their thirties, described lifetime involvement with 4-H and the horse industry, and most frequently reported having less than five years’ experience in their current position. The ground-level perspective of facilitators’ demographics and communication tendencies was evident in results of this study. In application, practitioners must continue to actively seek relationships with audiences, remain cognizant of communication factors, and provide accurate messaging through preferred channels.
Keywords: 4-H programs; Communications; Formative Evaluation; Horse; Volunteers